Angiotensin converting enzyme activity in infancy is related to birth weight - Forsyth, J (2004)
Aims: (a) To measure infant angiotensin converting enzyme (ACE) activity in healthy term infants at birth and during the first three months of life. (b) To determine the relation between serum ACE activity and infant feeding practice during this period. (c) To investigate the relation between serum ACE activity and birth weight and other potential contributing factors including acid-base status at birth, gestation, and maternal ACE genotype. Methods: Prospective study of term infants, with clinical and feeding data collected from parents and medical records, and serum ACE measured in the infant at birth and 1 and 3 months of age, and in the mother at the time of birth and one to three months after birth. Results: At birth and 1 and 3 months of age, infant serum ACE activity was twice that of maternal ACE activity. Infant ACE activity at birth and 1 and 3 months did not significantly differ between breast and formula fed infants. There was a highly significant negative correlation between infant ACE activity at 3 months and birth weight (r  =  –0.52; p < 0.001). This persisted after the conversion of birth weights to z scores (r  =  –0.34; p  =  0.03). ACE activity at 3 months was also related to placental weight (r  =  –0.30; p  =  0.02) and maternal age (r  =  –0.30; p  =  0.05). The strong correlation between serum ACE activity and birth weight z score persisted after adjustment for maternal age and placental weight (r  =  –0.34; p  =  0.03). Conclusion: As ACE is increasingly identified as a risk factor for cardiovascular disease, serum ACE activity in infancy may contribute to the link between low birth weight and later cardiovascular events.